2018
DOI: 10.14409/fa.v17i1.7651
|View full text |Cite
|
Sign up to set email alerts
|

Comparación De Técnicas De Análisis Multivariado Mediante Simulación Para Caracterización De Recursos Fitogenéticos en Función De Caracteres Susceptibles a Interacción Genotipo-Ambiente

Abstract: Los Recursos Fitogenéticos se conservan ex situ en bancos de germoplasma. Para que los mismos sean utilizados por los mejoradores deben ser caracterizados y evaluados. En el banco de Germoplasma del INTA Pergamino se realiza la caracterización y evaluación de poblaciones locales de maíz, donde los datos obtenidos pueden presentarse como matrices de tres vías (poblaciones * variable * ambiente). A partir de datos empíricos de tres vías se generaron datos simulados, los cuales se utilizaron para comparar las téc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Regarding the quantitative morphological and agronomic characterization of a set of populations in different environments, it is important to highlight that if the objective is to find the 'average' relationships between accessions, studies of empirical and simulated data have shown that performing a Principal Component Analysis on the mean of the environments gives similar results to the use of three-mode methods such as PGA, PCA-3modes or MFA [10][11][12][13], even when there is a moderate genotype-environment interaction. But if the intention is also to study this genotypeenvironment interaction, the three-mode methods are widely advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the quantitative morphological and agronomic characterization of a set of populations in different environments, it is important to highlight that if the objective is to find the 'average' relationships between accessions, studies of empirical and simulated data have shown that performing a Principal Component Analysis on the mean of the environments gives similar results to the use of three-mode methods such as PGA, PCA-3modes or MFA [10][11][12][13], even when there is a moderate genotype-environment interaction. But if the intention is also to study this genotypeenvironment interaction, the three-mode methods are widely advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…But its interpretation is not easy [16], and there is few software that do this, among them the R package tuckerR.mmgg [17]. The Escoufier Vectorial Correlation Coefficient (Rv) [18], which determines whether two configurations (scalar products) provide a similar image of individuals, taking values between zero (no similarity between the configurations) and one (the configurations are homothetic), can be used to quantify the degree of multivariate genotype-environment interaction [13].…”
Section: Discussionmentioning
confidence: 99%
“…L os recursos fitogenéticos asociados a la seguridad alimentaria y a los procesos agrícolas comprenden esa parte de la biodiversidad potencialmente útil y su relación con las especies silvestres, las cuales se deben conservar para garantizar alimentación a la población mundial (Zuliani et al, 2018).…”
Section: Introductionunclassified